Legal Analysis Related to Depreciation of Assets and Tax Liabilities of Fabric Shops in Cipadu Market, Tangerang - Bakhrudin, Bakhrudin; Margolang, Fahmi Ihsan (Westscience Press, 2023)
The fabric industry, a vital economic driver, relies on numerous small fabric shops to serve local communities and the broader textile supply chain. However, the complexities of managing asset depreciation and tax liability within these businesses are often underestimated. This research delves into the legal framework surrounding asset depreciation and tax liability as they pertain to fabric shops in Cipadu Market, Tangerang, Indonesia. By combining a mixed-methods approach involving surveys, interviews, and observations, this study investigates current practices, awareness of tax regulations, challenges faced, and opportunities for tax optimization among fabric shop owners. The results reveal a varied landscape where fabric shop owners predominantly employ the straight-line depreciation method and exhibit a reasonably high level of tax compliance. However, there exists a knowledge gap concerning specific tax incentives and a need for improved asset tracking and documentation practices. Moreover, a lack of financial expertise hampers the full utilization of tax optimization strategies. The study's findings offer valuable insights that extend beyond Cipadu Market and are applicable to small businesses in Indonesia and other emerging economies, emphasizing the importance of educational initiatives, simplified tax laws, and financial support for enhancing financial sustainability and compliance with the law.